The Effect of Topical Aloe Vera Gel Therapy on Phlebitis in Pediatric Patients - Sidik Syafaatullah; Agus Purnama; Siti Kamillah (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Introduction: Phlebitis, or inflammation of the veins, is a complication of intravenous (IV) therapy that can be caused by chemical substances, mechanical factors (such as IV equipment), or infections (due to microbial colonies from the catheter). It is characterized by pain, erythema, swelling, induration, and sometimes fever. Phlebitis can lead to further complications or worsen the patient’s condition, potentially extending their hospital stay. Managing phlebitis can be achieved through both pharmacological and non-pharmacological therapies, such as the use of aloe vera gel. Objective: This study aims to identify the effect of aloe vera gel therapy on reducing the level of phlebitis in pediatric patients. Method: The research design used a quasi-experimental non-equivalent control group design or non-randomized control group pretest-posttest design. The population consists of pediatric patients with IV infusions. A purposive sampling technique was used to select 58 children as the research sample. Data collection was conducted using observation sheets and then processed and analyzed using data processing applications with open-source statistical computer software jamovi version 2.4.8. The analysis test used the Wilcoxon-W test. Results: The study results showed a standard deviation average decrease in phlebitis levels among pediatric patients. The analysis test results revealed a P-value of 0.001 < 0.05 with an effect size of 1.00, indicating that aloe vera gel therapy significantly reduces phlebitis in children. Conclusion: There is a significant effect of aloe vera gel therapy before and after administration in the intervention group, and a significant difference between the intervention and control groups after the administration of aloe vera gel. So aloe vera gel is effective in treating phlebitis in children